The Effect of Atorvastatin (and Subsequent Metformin) on Adipose Tissue Acylation-Stimulatory-Protein Concentration and Inflammatory Biomarkers in Overweight/Obese Women With Polycystic Ovary Syndrome - Sathyapalan, Thozhukat; Hobkirk, James P.; Javed, Zeeshan; Carroll, Sean; Coady, Anne-Marie; Pemberton, Philip; Smith, Alexander; Cianflone, Katherine; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Background: Atorvastatin has been shown to improve cardiovascular risk (CVR) indices in women with polycystic ovary syndrome (PCOS). Low-grade chronic inflammation of adipose tissue may link PCOS and adverse CVR. In pro-inflammatory states such as PCOS, spontaneous activation of the alternative pathway of complement results in increased generation of acylation stimulating protein (ASP) from adipocytes irrespective of body mass index. Methods: The objective of this study was to determine the effect of atorvastatin on markers of adipose tissue dysfunction and inflammation; acylation-stimulating-protein (ASP), interleukin-6 (IL-6), and monocyte-chemoattractant-protein1 (MCP-1) in PCOS. This was a randomized, double-blind, placebo-controlled study where 40 medication-naive women with PCOS and biochemical hyperandrogenaemia were randomized to either atorvastatin 20 mg daily or placebo for 12 weeks. Following the 12 week randomisation; both group of women with PCOS were subsequently started on metformin 1500 mg daily for further 12 weeks to assess whether pre-treatment with atorvastatin potentiates the effects of metformin on markers of adipose tissue function We conducted a post hoc review to detect plasma ASP and the pro-inflammatory cytokines IL6 and MCP-1 before and after 12 and 24 weeks of treatment. Results: There was significant reduction in ASP (156.7 ± 16.2 vs. 124.4 ± 14.8ng/ml p <0.01), IL-6 (1.48 ± 0.29 vs.0.73 ± 0.34pg/ml p=0.01) and MCP-1 (30.4 ± 4.2 vs. 23.0 ± 4.5pg/ml p=0.02) after 12 weeks of atorvastatin that was maintained subsequently with 12 weeks treatment with metformin. There was a significant positive correlation between ASP levels with CRP (p<0.01), testosterone (p<0.01) and HOMA-IR (p<0.01); IL-6 levels with CRP (p <0.01) and testosterone (p<0.01) and MCP-1 with CRP (p<0.01); testosterone (p<0.01) and HOMA-IR (p<0.02). Conclusions: This post-hoc analysis revealed that 12 weeks of atorvastatin treatment significantly decreased the markers of adipose tissue dysfunction and inflammation, namely ASP, IL-6 and MCP-1 in obese women with PCOS. Changes in adipose tissue markers were significantly associative with substantial improvements in HOMA-IR, testosterone and hs-CRP levels.